Palaeomagnetic study of the El Quemado complex and Marifil formation, Patagonian Jurassic igneous province, Argentina - Iglesia Llanos, María Paula (2003)
The upper Jurassic El Quemado Complex was sampled at 36 sites from five localities in the cordilleran foothills of southern Patagonia between Lago Argentino and Lago Posadas–Sierra Colorada, and the middle Jurassic Marifil Formation at 12 sites in the Somuncur´a Massif near Camarones. The main lithology was ignimbrite, with minor tuff and lava. Petrographical and SEM observation show that the El Quemado rocks suffered an intense, high-temperature alteration which resulted in transformation of most primary Ti-magnetite in pseudobrookite, rutile and minor Ti-haematite and Fe hydrated oxides. A similar, less pronounced alteration occurred in the Marifil rocks. 40Ar/39Ar dating of El Quemadowas possible for one sample from Sierra Colorada and yielded an age of 156.5 ± 1.9 Ma. Magnetic mineralogy measurements (isothermal remanence, hysteresis loop, Curie balance) show that the remanent magnetization is dominated by PSD low-Ti magnetite, often associated to a minor high-coercive mineral (haematite). Secondary magnetization components are usually absent or weak at El Quemado sites, strong at Marifil. They were completely erased by thermal and AF demagnetization and a characteristic remanence (ChRM) stable up to temperatures higher than 550◦C or peak-field values of 100 mT was successfully isolated. The virtual geomagnetic pole (VGP) from the Marifil Formation (83◦S, 138◦E) is in agreement with the literature data for Jurassic rocks from stable South America. The El Quemado VGPs fall in two groups. The localities to the north of latitude 48◦S (Lago Posadas, Sierra Colorada) yield a VGP (81◦S, 172◦E) close to that of Marifil, whereas those south of latitude 49◦S (Lago San Mart´ın, Lago Argentino) show a highly elongated VGP distribution consistent with counter-clockwise block-rotation about vertical axes. These rotations were likely caused by thrust sheets which were rotating counter-clockwise at the same time they were advancing towards the foreland. The amount of rotation varies according to the location of the sampling sites in the thrust and fold belt.